PEMBERDAYAAN PETANI DALAM PEMBUATANPUPUK ORGANIK CAIR RAMAH LINGKUNGAN DARI SUMBERDAYA HAYATI DI LINGKUNGANNYA - Siti Umniyati, Tien Aminatun , (Universitas Negeri Yogyakarta, 2011)
Organic fertilizer is friendly to the environment. It can be made ofbioresources of the surroundings. The aims of this program were: 1) to givea course to the farmers to produce organic fertilizer; and 2) to see theeffectiveness of the course.The method of this programme was organizing a course for farmerswho lived at Pleret Village, Kecamatan Panjatan, Kulonprogo to produceorganic fertilizer from bioresources of their surroundings. They devided into5 groups and they all have practiced how to make N organic fertilizer, Porganic fertilizer, K organic fertilezer and bokashi fertilizer. They havepracticed how to aplly the organic fertilezer also.The result of the programme were: 1) The farmers have been giventhe knowledge and capability of producing organic fertilizer; and 2) Thecourse was effective.Keywords: empowering of farmers, organic fertilizer, bioresources